Analysis of the Influence of Leadership and Work Motivation on Employee Productivity at PT. X - Yusuf Yusuf; Aries Widya Gunawan (Rey Media Grafika, 2025)
This study aims to analyze the effect of leadership and work motivation on employee productivity at PT. X. The research method used is quantitative with a verificative approach, employing multiple linear regression analysis. The sample consists of 54 employees selected using random sampling. The results show that leadership does not have a significant effect on employee productivity (p > 0.05), while work motivation has a positive but marginal effect (p < 0.1). Simultaneously, leadership and work motivation do not significantly affect employee productivity (p > 0.05). The coefficient of determination (R²) value of 0.083 indicates that only 8.3% of the variation in employee productivity can be explained by these two variables. This study suggests that PT. X should improve leadership quality and focus on enhancing work motivation to increase employee productivity.